Faktor Pendukung PT Rayon Utama Makmur dalam Penghentian Proses Produksi Berdasarkan UU No. 11 Tahun 2020 tentang Cipta Kerja - Cosmas Primvance Daega Arya Putra; Waluyo Waluyo; Rosita Candrakirana (PLEDOI (Jurnal Hukum dan Keadilan), 2023)
The development of the industrial sector in Indonesia not only has a positive impact but also has a negative impact, especially in terms of environmental pollution. Environmental pollution that occurs can disturb and unsettle the community. The waste produced by PT Rayon Utama Makmur creates a pungent odor that is disturbing and disturbing the comfort of the community, especially those located behind the PT Rayon Utama Makmur factory. The standard criteria for environmental damage have been regulated in laws and regulations. Based on Law Number 11 of 2020 concerning Job Creation, the matter regarding PT Rayon Utama Makmur has been transferred to the Ministry of Environment and Forestry of the Republic of Indonesia so that the Sukoharjo Regency Environmental Service no longer has further authority regarding the continuation of this case. This study aims to analyze the factors that influenced PT Rayon Utama Makmur to finally decide to stop its production process and what PT Rayon Utama Makmur should do to be able to correct its mistakes. In this study, the authors used a normative empirical research method, which is a research method that combines elements of normative law supported by material data or empirical elements. Furthermore, good will and effort from PT Rayon Utama Makmur are needed to improve the production process and waste disposal process, because the relationship between PT Rayon Utama Makmur and local residents has deteriorated. The Central Government and Regional Governments also need to work together to review the way PT Rayon Utama Makmur treats the remaining production waste.